The Legal Consequences of Cancelling A Sale and Purchase Deed Made by A Temporary Land Deed Official - Tjandraningsih, Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to analyze the judge's considerations in decision number 121/Pdt.G/2015/PN.Pdg regarding the cancellation of a sale and purchase deed made by a Land Deed Official and its legal consequences. The research method used is normative juridical, utilizing secondary data as the primary data source. The sources of data consist of primary and secondary legal materials, collected through literature studies and interviews. The data analysis technique employed is qualitative analysis. The findings of the study include: (1) The sale and purchase deed in this case contains legal defects, as it does not meet the validity requirements of an agreement as stipulated in Article 1320 of the Indonesian Civil Code. As a result, the sale and purchase deed number 47/A.J.B/Sib.Sel/2007 is declared null and void by law. (2) The cancellation of a sale and purchase deed made by the Temporary Land Deed Official (PPATS) has the potential to lead to administrative and civil sanctions. In this case, the sanction imposed on the PPATS is the nullification of the issued deed. The parties involved, who have rights over the deed, should have taken legal measures following the deed's cancellation. However, in this case, the parties did not take any action regarding the annulled sale and purchase deed.